Regulation and Protection of Cloud Computing: Literature Review Perspective - Maskun, Maskun; Anwar, Rian Nugraha (Universitas Negeri Gorontalo, 2021)
Cloud computing is one of the developments of the internet of things. It can say that it is a new industry in era revolution 4.0. particular to store data, including customer data privacy. The research aims to determine some regulations and protection of cloud computing at either international or national levels. The research methods are normative legal research which applies some regulations both international and national legal instruments. The research results show that some international instruments can be seen in general and specific international instruments. The general instruments are such as the Universal Declaration of Human Rights 1948 (UDHR) and International Covenant on Civil and Political Rights 1996; the specific instruments are such as OECD Guidelines Governing the Protection of Privacy and Transborder Flows of Personal Data, 1980, Council of Europe Convention for the Protection of Individuals concerning the Processing of Personal Data, 1981, and United Nation General Assembly Resolution on the Right of Privacy in the Digital Age, 2014. In the Indonesian context, the regulation of it can be seen such as The Law No. 39 of 1999 Concerning Human Rights, The Law No. 14 of 2008 Concerning Public Information Disclosure, The Law No. 36 of 2009 Concerning Health, the Law No. 19 of 2016 concerning amendment of the Law No. 11 of 2008 concerning Information and Electronic Transaction and other sectoral regulation. Therefore, it can conclude that the need for regulation of cloud computing and its protection is needed to guarantee that those data are protected.